THE USE OF FLIP BOOKS AS LEARNING RESOURCES IN ARTS AND CULTURE SUBJECTS IN CLASS XI OF SMAN 5 KOTA SERANG - Nasiroh Nasiroh; Dwi Junianti Lestari; Syamsul Rizal (Universitas Pendidikan Indonesia, 2024)
TechTechnology currently plays an important role in teaching and learning activities, so teachers and students certainly have to take advantage of this technology to make it easier to find learning resources. One of the learning resources currently used by teachers and students in arts and culture subjects is the flip book learning resource which can be accessed via their respective cell phones. This study aims to determine the development of students in learning to use flip book learning resources, both in terms of cognitive, affective and psychomotor students. In this study, the method used is a qualitative descriptive method that can describe what is seen and based on existing phenomena. Based on the results of the research, the process of applying flip book learning resources to the subject of cultural arts aspects of dance has been carried out well. In addition, with the application of this learning resource, it can be seen that the level of student development in terms of cognitive, affective and psychomotor has started to improve and is increasing. So, it can be concluded that there is an influence of art and culture flip book learning resources on class XI students of SMA Negeri 5 Kota Serang.